High-strength high-thermal-stability lead-free solder alloy and preparation method and application thereof
By adding Ce and Ti elements and trace wetting balancers to the solder alloy, the problem of insufficient strength and thermal stability of existing solder alloys has been solved, and the development of high-strength and high-thermal stability lead-free solder alloys has been achieved. In the connection and packaging of new energy vehicles and high-power electronic devices.
Patent Information
- Application Number
- CN202411589664.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-08
- Publication Date
- 2025-02-07
- Estimated Expiration
- 2044-11-08
AI Technical Summary
The existing high-reliability solder alloys are still not sufficient to meet the high reliability requirements of new energy vehicles and high-power electronic equipment in terms of strength and thermal stability.
Using a high-strength, high-thermal stability lead-free solder alloy, its components include Ag, Cu, Sb, Bi, Ni, Ce, Ti and Sn elements. The thermodynamics of the alloy are improved by adding Ce and Ti elements and trace wetting balancers. and mechanical properties.
The lead-free solder alloy has a low interface compound growth rate in the temperature range from room temperature to 175°C, showing excellent reliability at high usage temperatures, and is suitable for high power semiconductor application scenarios.
Smart Images

Figure CN119387950A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of lead-free solder alloy component design and preparation, and in particular to a high-strength and high-thermal stability lead-free solder alloy and a preparation method and application thereof. Background Art
[0002] The concept of new energy vehicles first appeared in the 1970s to 1990s, when some research institutions and automakers began to develop electric vehicles and hybrid vehicles. However, due to factors such as battery technology and charging facilities, new energy vehicles have not been widely used. It was not until recent years that new energy vehicles entered a stage of rapid development. Governments of various countries have successively introduced a variety of incentive policies to promote the rapid development of the new energy vehicle industry chain. The market share of new energy vehicles has continued to increase, and my country's new energy vehicle-related industry chain has become the largest growth point for my country's current exports. With the rapid rise of new energy vehicles and the increasing degree of electrification of traditional fuel vehicles, higher requirements have been placed on the strength and thermal stability of automotive electronic solders.
[0003] Solder joints are the connection between electrical signals and mechanical connections in electronic systems. They play a vital role in electronic manufacturing and welding processes, and are directly related to the performance, reliability and safety of electronic equipment. According to statistics, more than 60% of quality accidents and failures of electronic products during manufacturing and service life are due to the aging of solder joints, and the basic root cause is defects in welding materials or processes. Under high-density processes, the mechanical, electrical and thermal loads borne by a unit solder joint increase exponentially, which puts forward new requirements for the temperature resistance of welding materials, solder joint strength, organizational stability and process operability.
[0004] Driven by the high-density packaging brought about by Moore's Law and the high strength and high thermal stability required by power semiconductors, the research and production of high-reliability solders have received extensive attention and investment abroad. As early as the 1990s, mainstream solder companies represented by Heraeus, Henkel, and Alpha began research on high-reliability solders for automotive electronics in advance and launched products represented by Inollot. Japanese companies such as Senju also conducted research and development and market promotion of high-reliability alloys based on the SnAgCu series of solders. However, existing research and applications have shown that although the existing high-reliability alloys have greatly improved in strength and thermal stability compared to SAC solders, there is still a small process window and poor compatibility with some materials. The strength and stability still need to be improved to adapt to the high-reliability service environment of new energy vehicles, power electronics, etc. Summary of the invention
[0005] The purpose of the present invention is to provide a high-strength and high-thermal stability lead-free solder alloy and a preparation method and use thereof. The solder alloy belongs to a high-strength and high-usage temperature lead-free soft solder. The alloy has better strength and thermal stability than the existing SnAgCuSbBiNi hexa-alloy, has a low interface compound growth rate at temperatures from room temperature to 175°C, and shows excellent reliability at high use temperatures.
[0006] The technical solution of the present invention is:
[0007] A high-strength and high-thermal stability lead-free solder alloy, the lead-free solder alloy comprises Ag, Cu, Sb, Bi, Ni, Ce, Ti and Sn elements, and the respective contents thereof are as follows by weight percentage: Ag 2.0-5.0%, Cu 0.01-0.7%, Sb 1.0-4.0%, Bi 1.0-5.0%, Ni 0.01-0.5%, Ce 0.01-1.0%, Ti 0.005-0.5%, and the balance is Sn; wherein Ce or Ti elements are one or more.
[0008] The high-strength and high-thermal stability lead-free solder alloy also includes a trace amount of wetting balance agent, which is one or more of Zn, Fe, Al, In, and Ba, and the total addition amount is 0.001-0.02% by weight.
[0009] The high-strength and high-thermal stability lead-free solder alloy preferably comprises 2.5-4.0% Ag, 0.03-0.6% Cu, 2.0-3.5% Sb, 2.0-4.0% Bi, 0.01-0.2% Ni, 0.01-0.5% Ce, 0.005-0.2% Ti, 0.001-0.005% trace wetting balance agent, and the balance is Sn.
[0010] The method for preparing the high-strength and high-thermal stability lead-free solder alloy comprises the steps of melting and mixing the metal single substances or the intermediate alloys of the elements according to the alloy ratio and then pouring the mixture to obtain the lead-free solder alloy.
[0011] In the preparation method of the high-strength and high-thermal stability lead-free solder alloy, during smelting, Sn and Bi elements are introduced in the form of metal single substances, and Ag, Cu, Sb, Ni, Ce, and Ti elements are introduced in the form of Sn-Ag alloy, Sn-Cu alloy, Sn-Sb alloy, Sn-Ni alloy, Sn-Ce alloy, and Sn-Ti alloy, respectively.
[0012] The method for preparing the high-strength and high-thermal stability lead-free solder alloy comprises the following steps: during smelting, single metal Sn, Sn-Cu alloy, Sn-Ag alloy, single metal Bi, Sn-Sb alloy, Sn-Ni alloy, Sn-Ce alloy and Sn-Ti alloy are added in sequence, and finally nano powder of a wetting balance agent is added.
[0013] The preparation method of the high-strength and high-thermal stability lead-free solder alloy is that the lead-free solder alloy is prepared by vacuum melting, and the melting furnace is evacuated to a pressure of 4×10 -3 ~6×10 -3 Pa.
[0014] The preparation method of the high-strength and high-thermal stability lead-free solder alloy comprises the following steps: melting and mixing the metal single substances or intermediate alloys of each element at a melting temperature of 400-600°C, and stirring the mixture for 30-60 minutes to reduce the temperature to 300°C; and covering the surface with an anti-oxidation flux during the melting process.
[0015] The high-strength and high-thermal-stability lead-free solder alloy is used as solder for electronic devices under high operating temperature and high reliability conditions.
[0016] The advantages and beneficial effects of the present invention are:
[0017] 1. For the SnAgCuSbBiNi hexa-alloy system, the present invention adds one or more of Ce and Ti elements in addition to the wetting balance agent to improve the thermodynamic and mechanical properties of the alloy, improve the reliability of the solder joint, and obtain a high-strength, high-use temperature lead-free soldering solder alloy. The present invention prepares a multi-component high-reliability solder alloy by using a wetting balance agent and added elements. The alloy has the characteristics of good process operability and can be used at higher ambient temperatures.
[0018] 2. The solder alloy of the present invention is a high-strength and high-thermal stability lead-free soft solder, which is particularly suitable for the connection and packaging of devices with high operating temperature, high power and high reliability requirements in high-power semiconductor application scenarios. It can be used in automotive electronics, shipbuilding, energy, aerospace and other fields. BRIEF DESCRIPTION OF THE DRAWINGS
[0019] Figure 1 The differential thermal analysis (DSC) curve of the SBNC solder alloy is shown in FIG. 1 , where the horizontal axis, Temperature, is the temperature (°C), and the vertical axis, Heat flow, is the heat flow rate (mW / mg).
[0020] Figure 2 The morphology of intermetallic compounds (IMC) at the interface of SBNC and SAC305 solder joints aged at 175℃ for 0h, 72h, 168h, 336h, and 672h. (ae) is SBNC; (fj) is SAC305. DETAILED DESCRIPTION
[0021] In a specific implementation process, the first aspect of the present invention provides a high-strength and high-thermal stability lead-free solder alloy, which comprises the following elements in weight percentage:
[0022] Ag 2.0~5.0%, Cu 0.01~0.7%, Sb 1.0~4.0%, Bi 1.0~5.0%, Ni 0.01~0.5%, Ce 0.01~1.0%, Ti 0.005~0.5%, trace wetting balance agent 0.001~0.02%, and the balance is Sn.
[0023] Furthermore, the lead-free solder alloy also contains Ag and Cu elements. The addition of Ag and Cu elements to the solder is to form a solder material based on the SnAgCu system, and the SnAgCu system material has a relatively low melting point. Furthermore, when the solder contains Ag and Cu elements, their respective contents in weight percentage are: Ag 2.0-5.0%, Cu 0.01-0.7%; preferably, Ag 2.5-4.0%, Cu 0.03-0.6%.
[0024] Furthermore, the lead-free solder alloy also contains Bi element. The most significant effect of adding Bi element to the solder is to reduce the melting point of the alloy and increase wettability. In addition, the dispersed Bi element can also play a certain strengthening role. Further, when the solder contains Bi element, its content is calculated by weight percentage: Bi 1.0-5.0%; preferably, Bi 2.0-4.0%.
[0025] Furthermore, the lead-free solder alloy also contains Sb element. Adding Sb element to the solder has the effect of lowering the melting point of the alloy and improving the strength of the solder joint by solid solution strengthening. Furthermore, when the solder contains Sb element, its content in weight percentage is: Sb 1.0-4.0%; preferably, Sb 2.0-3.5%.
[0026] Furthermore, the lead-free solder alloy also contains Ni element. Adding Ni element to the solder can improve the mechanical properties of the solder joint by forming intermetallic compound dispersion enhancement with Sn and Cu. At the same time, Ni element can also form intermetallic compound (IMC) at the interface, and improve the thermal stability of the solder joint by reducing the growth rate of IMC. Furthermore, when the lead-free solder alloy contains Ni element, its content is calculated by weight percentage: Ni 0.01-0.5%; preferably, Ni 0.01-0.2%.
[0027] Furthermore, the lead-free solder alloy also contains one or two of Ce and Ti elements. Adding Ce element to the solder can improve the high temperature resistance of the solder, so that the solder can still maintain stability in a high temperature environment, and reduce the risk of oxidation and deterioration during welding. Adding Ti element to the alloy can improve the strength of the solder and make the solder joint have better mechanical properties. Furthermore, when the solder contains Ce and Ti elements, their contents in weight percentage are: Ce 0.01-1.0%, Ti 0.005-0.5%; preferably, Ce 0.01-0.5%, Ti 0.005-0.2%.
[0028] Furthermore, the lead-free solder alloy also contains a trace amount of wetting balance agent. When the wetting balance agent is added to the solder, the wetting performance, viscosity after melting, fluidity, etc. of the alloy can be adjusted accordingly according to the type and amount of the added elements, thereby reducing the difficulty of alloy smelting and improving the solderability of the solder. Furthermore, when the solder contains a wetting balance agent, it includes but is not limited to nano powders such as Zn, Fe, Al, In, and Ba, and the total addition amount is calculated by weight percentage: 0.001-0.02%, preferably 0.001-0.005%.
[0029] The second aspect of the present invention provides a method for preparing a multi-component high-reliability lead-free solder alloy, and the specific technical route is as follows:
[0030] The preparation method of the lead-free solder alloy comprises the following steps:
[0031] According to a certain alloy ratio, the metal single substances or master alloys of each element are melted and mixed and then cast to obtain the multi-component lead-free solder alloy; wherein:
[0032] During alloy smelting, Sn element is introduced in the form of metal element;
[0033] During alloy smelting, Bi element is introduced in the form of metal element;
[0034] When the alloy is smelted, the Ag element is introduced in the form of Sn-Ag master alloy;
[0035] During alloy smelting, the Cu element is introduced in the form of Sn-Cu master alloy;
[0036] During alloy smelting, the Ni element is introduced in the form of Sn-Ni master alloy;
[0037] During alloy smelting, the Sb element is introduced in the form of Sn-Sb master alloy;
[0038] During alloy smelting, the Ce element is introduced in the form of Sn-Ce master alloy;
[0039] During alloy smelting, the Ti element is introduced in the form of Sn-Ti master alloy.
[0040] During smelting, single metal Sn, Sn-Cu alloy, Sn-Ag alloy, single metal Bi, Sn-Sb alloy, Sn-Ni alloy, Sn-Ce alloy, and Sn-Ti alloy are added in sequence, and a wetting balance agent is added.
[0041] Furthermore, the intermediate alloy is prepared by vacuum melting; wherein the melting furnace is evacuated to a pressure of (4-6)×10 -3 Pa.
[0042] Furthermore, the melting temperature of the metal single substance or alloy of each element is 400-600°C, and the temperature is kept and stirred for 30-60 minutes, and then dropped to 300°C; during the melting process, the surface is covered with an anti-oxidation flux.
[0043] Furthermore, the surface oxide slag is removed and the ingot is cast into a mold to prepare a multi-component solder alloy ingot.
[0044] The present invention is further described below in conjunction with the accompanying drawings and specific embodiments, but the protection scope of the present invention is not limited to the contents described.
[0045] Example 1
[0046] In this embodiment, a lead-free solder alloy SnAgCuSbBiNiCe (SBNC) is used, and its components are as follows by weight: Ag 3.0%, Cu 0.5%, Sb 3.0%, Bi 3.2%, Ni 0.01%, Ce 0.05%, the wetting balance agents are Zn, Al, In and the content is 0.001% respectively, and the balance is Sn.
[0047] The preparation method of the lead-free solder alloy comprises the following steps:
[0048] (1) Preparation of master alloy: Add single metal Sn and Ag with a purity of 99.99wt% according to the required alloy ratio into a medium frequency induction melting furnace for melting, and evacuate the furnace to a pressure of 5×10 -3 Pa, heated to 1100℃ and kept warm for 1 hour, cooled to 400℃ and poured into a mold to prepare Sn-Ag master alloy. Sn-Cu was melted in a medium frequency induction melting furnace at 1150℃ and kept warm for 1 hour, cooled to 400℃ and poured into a mold. Sn-Sb master alloy was melted in a vacuum resistance furnace and evacuated to a pressure of 4×10 -3 Pa, smelting temperature is 660℃, stirring is maintained for 1 hour, and casting temperature is 400℃. Sn-Ni master alloy is smelted in medium frequency induction furnace, and vacuum is drawn to the pressure of 5×10 -3Pa, heated to 1250℃ and kept warm for 1 hour, cooled to 400℃ and poured. Sn-Ce master alloy was melted in a vacuum resistance furnace and evacuated to a pressure of 6×10 -3 Pa, the smelting temperature is 1050℃, the mixture is kept warm and stirred for 1 hour, and the casting temperature is 400℃.
[0049] (2) Preparation of SnAgCuSbBiNiCe solder alloy ingot: single metal Sn, Bi and the master alloys Sn-Ag, Sn-Cu, Sn-Sb, Sn-Ce and Sn-Ni obtained in step (1) are added into a smelting furnace in the order of single metal Sn, master alloy Sn-Ag, master alloy Sn-Cu, single metal Bi, master alloy Sn-Sb, master alloy Sn-Ni and master alloy Sn-Co according to the required alloy ratio, and wetting balance agents Zn, Al and In nanopowders are added. During the smelting process, rosin is covered on the surface, and the mixture is heated to 400° C., kept warm and stirred for 40 minutes, and then the surface covering and oxide slag are removed, the mixture is cooled to 300° C., and poured into a mold to prepare SnAgCuSbBiNiCe solder alloy ingot.
[0050] (3) The melted alloy was subjected to DSC test, and the melting point was 210.16°C. Figure 1 The tensile strength of the alloy is 57.4MPa, which is more than 70% higher than that of SAC305.
[0051] (4) The smelted alloy was used to prepare sandwich structure welds, and the welds were aged at 175°C for 0 h, 72 h, 168 h, 336 h, and 672 h, respectively. SAC305 was used as the reference group, and the samples with different aging times were mounted with resin. After grinding and polishing, the weld microstructure was observed under a scanning electron microscope. Figure 2 As shown in the figure, the IMC morphology at the interface of SnAgCuSbBiNiCe and SAC305 solder joints aged at 175℃ for 0h, 72h, 168h, 336h, and 672h. It can be seen that the interface compound layer of the SnAgCuSbBiNiCe alloy solder joint is thinner and relatively flatter than that of SAC305. By fitting the relationship between IMC thickness and time, it can be seen that the growth rate of IMC of SnAgCuSbBiNiCe alloy solder is lower than that of SAC305, and it has good thermal stability.
[0052] The method for preparing the lead-free high reliability solder in Examples 2 to 8 is the same as that in Example 1, except that the weight ratio of each element is different. In step (1), the intermediate alloy smelting step is the same. In step (2), the corresponding proportions of Bi single alloy, Sn-Sb, Sn-Ce intermediate alloy and other components and pure Sn are weighed and smelted according to the final designed composition. Wherein:
[0053] Example 2
[0054] In this embodiment, the weight percentage of the lead-free solder alloy composition is: Ag 5.0%, Cu 0.5%, Sb 2.0%, Bi 1.0%, Ni 0.1%, Ce 0.01%, and the balance is Sn. When preparing the lead-free solder alloy, the melting temperature of the metal single substance or alloy of each element is 500°C, and it is kept warm and stirred for 60 minutes, then the surface covering and oxide slag are removed, the temperature is lowered to 300°C, and it is poured into a mold to prepare a SnAgCuSbBiNiCe solder alloy ingot. The melting temperature of the lead-free solder alloy is 223.2°C, and the tensile strength reaches 52.1MPa.
[0055] Example 3
[0056] In this embodiment, the weight percentage of the lead-free solder alloy composition is: Ag 2.0%, Cu 0.7%, Sb 2.0%, Bi 4.0%, Ni 0.5%, Ce 0.5%, and the balance is Sn. When preparing the lead-free solder alloy, the melting temperature of the metal single substance or alloy of each element is 400°C, and it is kept warm and stirred for 50 minutes, then the surface covering and oxide slag are removed, the temperature is lowered to 300°C, and it is poured into a mold to prepare a SnAgCuSbBiNiCe solder alloy ingot. The melting temperature of the lead-free solder alloy is 216.4°C, and the tensile strength is 47.1MPa.
[0057] Example 4
[0058] In this embodiment, the weight percentage of the lead-free solder alloy components is: Ag 3.0%, Cu 0.5%, Sb 4.0%, Bi 2.8%, Ni 0.05%, Ce 0.01%, and the balance is Sn. When preparing the lead-free solder alloy, the melting temperature of the metal single substance or alloy of each element is 600°C, and it is kept warm and stirred for 40 minutes, then the surface covering and oxide slag are removed, the temperature is lowered to 300°C, and it is poured into a mold to prepare a SnAgCuSbBiNiCe solder alloy ingot. The melting temperature of the lead-free solder alloy is 219.1°C, and the tensile strength reaches 52.3MPa.
[0059] Example 5
[0060] In this embodiment, the weight percentage of the lead-free solder alloy components is: Ag 3.0%, Cu 0.5%, Sb 2.0%, Ni 0.05%, Bi 3.0%, Ce 0.03%, and the balance is Sn. When preparing the lead-free solder alloy, the melting temperature of the metal single substance or alloy of each element is 400°C, and it is kept warm and stirred for 40 minutes, then the surface covering and oxide slag are removed, the temperature is lowered to 300°C, and it is poured into a mold to prepare a SnAgCuSbBiNiCe solder alloy ingot. The melting temperature of the lead-free solder alloy is 217.6°C, and the tensile strength reaches 54.6MPa.
[0061] Example 6
[0062] In this embodiment, the weight percentage of the lead-free solder alloy components is as follows: The method for preparing the lead-free high-reliability solder is the same as that in Embodiment 1, except that the element Ti is added. The alloy is calculated by weight percentage as follows: Ag 3.0%, Cu 0.5%, Sb 2.0%, Bi 3.0%, Ni 0.05%, Ce 0.02%, Ti 0.005%, the wetting balance agent is Ba and In (added in the form of nano powder) and the content is 0.001% respectively, and the balance is Sn. When preparing the lead-free solder alloy, the intermediate alloy smelting step in step (1) is the same, and the smelting of the Sn-Ti intermediate alloy is added in step (2): the Sn-Ti intermediate alloy and other components and pure Sn in the corresponding proportion are weighed and smelted according to the final design composition, and the Sn-Ti intermediate alloy is smelted in a vacuum resistance furnace, and the vacuum is evacuated to a pressure of 4×10 -3 Pa, smelting temperature is 1100℃, heat preservation and stirring for 1 hour, casting temperature is 400℃, and Sn-Ti master alloy is prepared. The melting temperature of the metal single substance or alloy of each element is 600℃, heat preservation and stirring for 60min, then the surface covering and slag are removed, the temperature is lowered to 300℃, and poured into a mold to prepare SnAgCuSbBiNiCeTi solder alloy ingot. The melting temperature of the lead-free solder alloy is 219.7℃, and the tensile strength is 71.2MPa.
[0063] Example 7
[0064] In this embodiment, the weight percentage of the lead-free solder alloy components is: Ag 3.0%, Cu 0.5%, Sb2.0%, Bi 3.0%, Ni 0.05%, Ce 0.05%, Ti 0.01%, and the balance is Sn. When preparing the lead-free solder alloy, the melting temperature of the metal single substance or alloy of each element is 600°C, and it is kept warm and stirred for 60 minutes, then the surface covering and oxide slag are removed, the temperature is lowered to 300°C, and it is poured into a mold to prepare a SnAgCuSbBiNiCeTi solder alloy ingot. The melting temperature of the lead-free solder alloy is 221.3°C, and the tensile strength is 77.5MPa.
[0065] Example 8
[0066] In this embodiment, the weight percentage of the lead-free solder alloy components is: Ag 3.0%, Cu 0.5%, Sb2.0%, Bi 3.0%, Ni 0.05%, Ce 0.05%, Ti 0.2%, and the balance is Sn. When preparing the lead-free solder alloy, the melting temperature of the metal single substance or alloy of each element is 600°C, and it is kept warm and stirred for 60 minutes, then the surface covering and oxide slag are removed, the temperature is lowered to 300°C, and it is poured into a mold to prepare a SnAgCuSbBiNiCeTi solder alloy ingot. The melting temperature of the lead-free solder alloy is 224.5°C, and the tensile strength reaches 65.3MPa.
[0067] It can be seen from the above embodiments that the solder alloy of the present invention is a high-strength and high-thermal-stability lead-free solder, and its melting temperature can reach 210-225°C, and its tensile strength can reach 45-80MPa. It is particularly suitable for the connection and packaging of devices with high operating temperature, high power, and high reliability requirements in high-power semiconductor application scenarios, and can be used in automotive electronics, ships, power electronics, aerospace and other fields.
Claims
1. A high-strength and high-thermal stability lead-free solder alloy, characterized in that: The lead-free solder alloy comprises Ag, Cu, Sb, Bi, Ni, Ce, Ti and Sn elements, and the content of each of them is as follows by weight percentage: Ag 2.0-5.0%, Cu 0.01-0.7%, Sb 1.0-4.0%, Bi 1.0-5.0%, Ni 0.01-0.5%, Ce 0.01-1.0%, Ti 0.005-0.5%, and the balance is Sn; wherein Ce or Ti elements are one or more.
2. The high-strength and high-thermal-stability lead-free solder alloy according to claim 1, characterized in that: It also includes a trace amount of wetting balance agent, which is one or more of Zn, Fe, Al, In, and Ba, and the total addition amount is 0.001-0.02% by weight.
3. The high-strength and high-thermal-stability lead-free solder alloy according to claim 2, characterized in that: Preferably, Ag is 2.5-4.0%, Cu is 0.03-0.6%, Sb is 2.0-3.5%, Bi is 2.0-4.0%, Ni is 0.01-0.2%, Ce is 0.01-0.5%, Ti is 0.005-0.2%, a trace amount of wetting balance agent is 0.001-0.005%, and the balance is Sn.
4. A method for preparing the high-strength and high-thermal-stability lead-free solder alloy according to any one of claims 1 to 3, characterized in that: The lead-free solder alloy is obtained by melting and mixing the metal single substances or the intermediate alloys of the elements according to the alloy ratio and then pouring.
5. The method for preparing a high-strength and high-thermal-stability lead-free solder alloy according to claim 4, characterized in that: During smelting, Sn and Bi elements are introduced in the form of metal elements, and Ag, Cu, Sb, Ni, Ce, and Ti elements are introduced in the form of Sn-Ag alloy, Sn-Cu alloy, Sn-Sb alloy, Sn-Ni alloy, Sn-Ce alloy, and Sn-Ti alloy, respectively.
6. The method for preparing a high-strength and high-thermal-stability lead-free solder alloy according to claim 5, characterized in that: During smelting, single metal Sn, Sn-Cu alloy, Sn-Ag alloy, single metal Bi, Sn-Sb alloy, Sn-Ni alloy, Sn-Ce alloy, and Sn-Ti alloy are added in sequence, and finally the nano powder of the wetting balance agent is added.
7. The method for preparing a high-strength and high-thermal-stability lead-free solder alloy according to claim 5, characterized in that: The lead-free solder alloy is prepared by vacuum melting. The melting furnace is evacuated to a pressure of 4×10 -3 ~6×10 -3 Pa.
8. The method for preparing a high-strength and high-thermal-stability lead-free solder alloy according to claim 5, characterized in that: The melting temperature of the metal single substance or the intermediate alloy of each element is 400-600°C, and the mixture is stirred for 30-60 minutes and then reduced to 300°C; during the melting process, the surface is covered with an anti-oxidation flux.
9. Use of the high-strength and high-thermal-stability lead-free solder alloy according to any one of claims 1 to 8 as solder for electronic devices under high operating temperature and high reliability conditions.
Citation Information
Patent Citations
Lead-free soldering material and preparing method thereof
CN103831543A
Laminated composite made up of an electronic substrate and an arrangement of layers comprising a reaction solder
CN103842121A
Metal substrate with plating
CN105774118A
Low temperature high reliability tin alloy for soldering
CN106660153A
Lead-free solder
CN114289927A
Cited By
Sn-Ag-Cu-Zn-X series lead-free brazing filler metal with high strength and high plasticity as well as preparation method and application of Sn-Ag-Cu-Zn-X series lead-free brazing filler metal
CN121083182A